2010
DOI: 10.1073/pnas.1012896107
|View full text |Cite
|
Sign up to set email alerts
|

A seed coat bedding assay shows that RGL2-dependent release of abscisic acid by the endosperm controls embryo growth in Arabidopsis dormant seeds

Abstract: Seed dormancy is an ecologically important adaptive trait in plants whereby germination is repressed even under favorable germination conditions such as imbibition with water. In Arabidopsis and most plant species, dormancy absolutely requires an unidentified seed coat germination-repressive activity and constitutively higher abscisic acid (ABA) levels upon seed imbibition. The mechanisms underlying these processes and their possible relationship are incompletely understood. We developed a "seed coat bedding" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
169
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 43 publications
9
169
2
Order By: Relevance
“…1 and Supplementary Table 1). It has been established that germination is ultimately initiated within the Arabidopsis embryo and that this process is informed by the endosperm (10,12,21,22). The cellular locations underlying this decision-making process remain unknown, however.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Supplementary Table 1). It has been established that germination is ultimately initiated within the Arabidopsis embryo and that this process is informed by the endosperm (10,12,21,22). The cellular locations underlying this decision-making process remain unknown, however.…”
Section: Resultsmentioning
confidence: 99%
“…AtGASA6 Is Located Downstream of RGL2 to Integrate Glc and GA Signaling Because RGL2 plays an essential role in integrating GA and ABA signaling during seed germination (Piskurewicz et al, 2008;Lee et al, 2010) and because our results suggest that AtGASA6 plays an integral role in Glc, ABA, and GA signaling pathways and functions downstream of RGL2 in GA pathway, we hypothesized that the response of AtGASA6 to Glc and GA is also regulated by RGL2. To verify this, mutant seeds of rgl2-13, rgl2-13/gasa6-1, and gasa6-1 were , and GIN2 in the GA, ABA, and Glc signaling pathways.…”
Section: Atgasa6 Is a Positive Regulator Of Seed Germination Under Stmentioning
confidence: 94%
“…The roles of ABA in modulating seed development, dormancy, germination, and plant adaptation to abiotic environmental stresses, have been well studied (Gubler et al, 2005;Finkelstein et al, 2008), and it has been found that ABA specifically inhibits endosperm rupture rather than testa rupture in the seed germination process (Müller et al, 2006;Lee et al, 2010). ABA signaling components include ABSCISIC ACID-INSENSITIVE3 (ABI3), which encodes a B3 domain transcription factor, and ABI5, encoding a basic Leu zipper transcription factor, both of which are necessary for growth arrest when germinating seeds encounter unfavorable conditions (Giraudat et al, 1992;Finkelstein and Lynch, 2000).…”
mentioning
confidence: 99%
“…Both dormant and nondormant seeds show a decline in their ABA levels within the first 12 h of imbibition. Thereafter, dormant seeds show consistently higher ABA levels than nondormant seeds (Ali-Rachedi et al, 2004;Lee et al, 2010). We studied the expression kinetics of ABA and GA metabolic genes during imbibition of fresh mature Ler, dog1-1, and NIL DOG1 seeds in detail.…”
Section: Dog1 Influences the Expression Of Aba And Ga Metabolic Genesmentioning
confidence: 99%